Investigation of porcupine bezoar extract combined with electroporation on HeLa cell - Azizulkarim, Azra Hazwanie; Abdul Jamil, Muhammad Mahadi; Tengku Ibrahim, Tengku Nadzlin; Hamdan, Salehhuddin; Baba, Sayang; Abdul Wahab, Ridhwan (Institute of Electrical and Electronics Engineers Inc., 2019)
Current chemo-preventive agents will causes a long term side effects in cancer sufferer. Therefore, this research focusses on the benefits of combine both technique of Electroporation (EP) method and with natural animal extract in process to inhibit the proliferation of cancer cell, as a solution to reduce or adverse effects of orthodox drugs. The present study indicates on anti-cancer potentially of Porcupine Bezoar Extract (PBE), also known as Hystrix Brachyuran against HeLa cell. Cell viability of HeLa cell were determined after HeLa cell treated with 500 V/cm and pulse duration of 100µs before the concentration of 80.0 µg/ml of Porcupine Bezoar Extract (PBE) was added into the cell. The cell viability and cell growth were monitored up to 48 hours with comparative to untreated cell as a control group.This study result proved that by combine both technique; Electroporation (EP) and with natural animal extract Porcupine Bezoar Extract (PBE) might open the door and it has an ability in supressing the growth of HeLa cell.